Relative Humidity And Temperature Effect On Biological Contaminant At Public Access Building In Seberang Perai Selatan, Pulau Pinang - Nazir, Amni Umirah Mohamad (Universiti Sains Malaysia, 2017)
Generally, 90% of people spends their time indoor. In ICOP (2010) also stated that healthy indoor will produce better work environment. Furthermore, recent findings had shown that high biological contaminated could lead to Sick Building Syndrome (SBS). This study aims to determine the level of temperature, relative humidity and its relationship with biological contaminants in mosques as stipulated in Industry Code of Practice (ICOP), 2010. Biological contaminants relationship between provenances temperature (T) and relative humidity (RH) were identified. An investigation of six public access building regarding T, RH and biological contaminants were done at Masjid Bukit Panchor, Masjid Nibong Tebal, Masjid Baru Sungai Bakap, Masjid Sungai Setar Besar, Masjid Kampung Besar and Masjid Telok Ipil. Result of the study shown that level of T and RH in the public access building were influenced by the number of jemaah and mechanical ventilation. Masjid Nibong Tebal was one of the high temperature (32°C) mosque with a high number of jemaah, meanwhile Masjid Kampung Besar also had the highest temperature (33°C) because of the passive ventilation. Besides that, Masjid Baru Sungai Bakap had the highest average RH (74%) which exceed the ICOP limit. Further, the average concentrations of mold contaminants for all monitored mosques did not exceed the acceptable guideline limit. Meanwhile, Masjid Telok Ipil was the only mosque that had the highest bacterial count which exceed the acceptable limit with 620 cfu/m³ after vacuuming the carpets. Temperature and relative humidity were not only sources for microbial growth but human activities and carpeting are also one of the main contributors.